2006
DOI: 10.1080/01919510600900290
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Degradation of Biological Macromolecules: Proteins, Hemoglobin, RNA, and DNA

Abstract: The reactions of ozone with a series of biological macromolecules are reviewed. With proteins, ozone causes the oxidation or the ozonolysis of certain amino acid residues, for instance, tryptophan, tyrosine and cysteine. As a result of this attack the protein molecules undergo changes in their usual folding and binding ability and are denaturated as shown by polarimetric or chirooptical measurements and by the inhibition of their biological activity. In any case viscosimetric measurements show that the amide b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 18 publications
2
37
0
1
Order By: Relevance
“…Ozone has been reported to target susceptible amino acids, such as cysteine, methionine, tryptophan, tyrosine, histidine, cystine, and phenylalanine, affecting the primary structure of the infectious prion protein (38). The oxidation and cleavage of selected amino acids or monomeric units can induce modifications of the primary structure or significant changes in the secondary, tertiary, and quaternary structure or hinder protein folding abilities (39). The effect of pH on PrP Sc inactivation by ozone was significant (P Ͻ 0.05) at both 4 and 20°C, and PrP Sc was inactivated more rapidly at pH 4.4 than at pH 6.0 and 8.0.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone has been reported to target susceptible amino acids, such as cysteine, methionine, tryptophan, tyrosine, histidine, cystine, and phenylalanine, affecting the primary structure of the infectious prion protein (38). The oxidation and cleavage of selected amino acids or monomeric units can induce modifications of the primary structure or significant changes in the secondary, tertiary, and quaternary structure or hinder protein folding abilities (39). The effect of pH on PrP Sc inactivation by ozone was significant (P Ͻ 0.05) at both 4 and 20°C, and PrP Sc was inactivated more rapidly at pH 4.4 than at pH 6.0 and 8.0.…”
Section: Discussionmentioning
confidence: 99%
“…Knight and Mudd (2004) stated that the aromatic amino acids tryptophan, are oxidized by ozone causing the degradation of the relative moiety. The most sensitive amino acid to ozone is tryptophan which is degraded (Cataldo 2006). The oxidation of lipid and proteins have structural and functional roles in biomembranes, could alter the ability to regulate permeability (Komanapalli and Lau 1996).…”
Section: Lipid and Tryptophan Oxidation Of F Oxysporiummentioning
confidence: 99%
“…Ozone reacts predominantly with guanine or thiamine moieties in nucleic acids (Komanapalli and Lau 1996). The action of ozone occurs by cell lysing or rupture of cell walls with interaction of ozone with key biopolymers (proteins and nucleic acids) present in biological environments, where Tryptophan was the most reactive amino acid towards ozone followed by tyrosine while phenylalanine appears much less reactive (Cataldo 2006).…”
Section: Lipid and Tryptophan Oxidation Of F Oxysporiummentioning
confidence: 99%
“…It should be noticed also that gelatine contains only small amounts of the most ozone reactive amino acids like methionine, tyrosine, cystine and phenylalanine [14,15]. Thus, although these residues will be oxidized first by the action of O 3 on gelatine, because of their minimal presence in the gelatin macromolecule, it can be shown that the theoretical optical activity of the gelatin will not change significantly.…”
Section: Optical Activity Of Gelatin and Polarimetric Measurements Dumentioning
confidence: 99%
“…Including in this calculation even the ozone reactive amino acids arginine and hystidine, the [α] theoretical remains equal to −21. However, from the practical side, the oxidation of the mentioned amino acid residues, even in relatively small amount certainly affects the tertiary structure of the protein causing a reduction in the gelatin optical activity [14,15]. Although ozone does not cause the chain scission of the proteins because it is not reactive toward the amide bond [14,15], the structural changes of some amino acid residues along the protein chains must necessarily affect the tertiary structure of the protein causing a reduction of the experimental specific optical rotation as shown in Fig.…”
Section: Optical Activity Of Gelatin and Polarimetric Measurements Dumentioning
confidence: 99%